Penerapan Budaya Kaizen (5R) Sebagai Upaya Peningkatan Mutu Pelayanan Di Rumah Sakit - Leo Pratama Agung; Dety Mulyanti (Jurnal Medika Nusantara, 2023)
Quality health services is one measure of satisfaction effect on the patient's desire to return to the institution that provides it effective health services. To meet the needs and desires of patients so that satisfaction can be obtained in the end can increase trust in the hospital through excellent service. One of the important issues to answer the strategy in the midst of a situation of decreased public trust in hospital services is "What is the operational strategy in improving quality, service value, patient satisfaction, cost efficiency, service process effectiveness, reducing "waste", and cultural management in hospitals ?”. So what can be a mindset approach to implementing this is "Kaizen (5R)". This approach can be a tool for cultivating a culture of change directed at increasing the value of patient care (customer value) simultaneously with efficiency efforts. The implementation of 5R can be carried out in line with increasing discipline in the environment around the workplace, starting with simplifying the storage of the equipment needed in the work environment, tidying up the arrangement, cleaning, caring for and caring for it and doing it continuously will make it a pleasant workplace through the formation of work discipline.